Transformation of Commercial Archives Data Center in Serving the Availability of Information for the Community (Open Society Conference, 2023)
With the development of life in society, including the various types of social changes that occur, the community's need for data services is increasing. Initially the data obtained can be obtained through various agency databases. However, because of the wide variety of archival data requirements, specialized commercial archival databases are built by individuals or organizations. The purpose of this study is to identify the types of commercial archive data centers, their characteristics and service models. The method used in this study was a literature review compiled from various sources related to the research objectives. Then the data is codified, compiled and analyzed. The results of the study show that the increasing activities that occur in the community, special data are needed, such as data related to economic development, domestic trade data, cultural data centers and others. In this study, the sample chosen to build a commercial archive data center is cultural archive data which includes various superior products from various regions in Indonesia. Among these superior products are products that can improve the economy in society. Archive data that is complete and easy to find will provide benefits for various parties to utilize the archival data.